STUDY ON BODY WEIGHT AND SCROTAL CIRCUMFERENCE AND ITS CORRELATIONS WITH SEMEN PRODUCTION TRAITS IN CROSSBRED JERSEY BULLS - Gopinath, A; Sivasalem, SN; Karthicayan, SM; Venkatraman, R; Kulasekar, K (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
The present study was aimed to investigate the effects of body weight and scrotal circumference on semen production traits of 136 crossbred Jersey bulls, which were maintained at three frozen semen stations of Tamil Nadu, India. Semen production traits such as semen volume, sperm concentration, mass activity, initial sperm motility, post-thaw motility and number of doses per ejaculate were taken for this study. The overall mean values for semen volume (ml), sperm concentration (millions per ml), mass activity (0 to 5 scale), initial sperm motility (per cent), post thaw motility (per cent) and number of doses per ejaculate were 4.18 ± 0.02, 1052.80 ± 7.26, 2.09 ± 0.07, 63.36 ± 0.00, 50.52 ± 0.00 and 215.50 ± 2.01 respectively. From this study, it revealed that the body weight and scrotal circumference of bulls significantly influenced all semen production traits except mass activity. Bulls having a body weight between 350 to 550 kg produced better quality semen and more number of frozen semen doses per ejaculate. When the scrotal circumference was >36 cm, majority of the semen production traits showed better values. The body weight was positively and significantly correlated with scrotal circumference, Semen volume and number of frozen semen doses produced per ejaculate. The scrotal circumference was positively and significantly correlated with semen volume, mass activity and number of doses per ejaculate; negatively and significantly correlated with initial sperm motiltiy.
Keywords: Scrotal circumference; Crossbred Jersey bulls; Semen production traits